Evaluation of Drainage Network System (Case Study of Pangkajene Kepulauan State Agricultural Polytechnic Campus Area) - Aulia, Nur; Alham, Irawan; Paharuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to identify the condition of highway drainage channels and evaluate the existing highway drainage network system in accommodating runoff discharge, channel dimensions and flow direction in channels that occur inundation in the Pangkajene Islands State Agricultural Polytechnic Campus area which is expected to help solve flooding problems in the area. The research method used is descriptive quantitative, which is a method of calculation and description of the results of field data processing. Secondary data collection includes; rainfall data for the last 10 years, obtained from the Department of Resources; topographic maps, drainage network maps and situation maps, obtained from the Politani Pangkep Campus planning section. Primary data collection is obtained from direct measurements in the field using a Waterpass measuring instrument to measure elevation and channel length. The results of this study found that the drainage capacity < 2-year and 5-year return period Plan Flood Discharge, so planning is needed to increase drainage capacity